Bridging Academia and Accountancy Practice: Insights from Saudi Southern Region Academics - Alshahrani, Sami; Albader, Mohammed; Tamanna Ahamed, Fatematuz; Alhaider, Masoud (مجلة العلوم الإدارية و الإقتصادية, 2025)
Enhancing the relationship between academia and professional accounting bodies is critical for developing professional accountants and making them ready for real-world challenges. Not only that, it will also reflect positively on the advancement of the accounting profession. This study explores the interrelationship and the extent of collaboration between accounting education and the professional accounting body in the Kingdom of Saudi Arabia, particularly focusing on the Southern region of the kingdom and aiming to provide recommendations that will contribute to the development of the accounting profession. To achieve this objective, a quantitative design was employed, using a questionnaire and covering accounting academics. The data analysis was performed using the Statistical Package for the Social Sciences (SPSS). The findings indicated that of all participants believe in the importance of collaboration between academic institutions and the professional accounting body in Saudi. In addition, the findings reveal that almost of the participants believe there is a significant gap between academic curricula and the needs of professional practice. This gap is attributed to factors such as outdated accounting curricula, limited integration of practical skills, and insufficient collaboration with the Saudi Organization for Chartered and Professional Accountants (SOCPA). The study recommends enhancing academic curricula, increasing practical training opportunities, and fostering collaboration between universities and SOCPA to better align academic programs with professional requirements.